Diversidade de peixes residentes em cabeceiras de rios. Uma abordagem cromossômica em três diferentes biomas aquáticos da Região Sul do Brasil - Vicari, Marcelo Ricardo (2006)
This study presented cytogenetic analysis of small fishes species collected in the headwaters of Jaguariaíva, Ribeira and, Tibagi rivers. Some of these species have had a comparative cytogenetic population analysis among different basins, while in the others were observed inherent specific problems only in one population. In this work we boarded cytogenetic, cytotoxonomy, biogeographic and evolutive biology aspects of these populations: Corydoras paleatus, Corydoras ehrhardti, Apareiodon sp., Geophagus brasiliensis, Cichlasoma facetum, Astyanax scabripinnis species complex, Astyanax janeiroensis, and Characidium sp. cf. C. gomesi. Here we discussed and presented (a) the sympatric occurrence of C. paleatus and C. ehrhardti from Dourada lagoon, Tibagi basin; (b) a ZZ/ZW sex chromosome system in an undescribed species of the genus Apareiodon in the Verde river, Tibagi basin (c) the karyotypic conservadorism visualized in species and populations of Perciformes, G. brasiliensis and C. facetum, in the Jaguariaíva, Ribeira and Tibagi basins, showing the dispersion of fish species hypotheses among these basins; (d) a comparative cytogenetic analysis of A. scabripinnis species complex, among Jaguariaíva, Ribeira, and Tibagi basins, all of them shared karyotypes with 2n=50 chromosomes but minors differences among them were observed, and we also showed a sympatric cytotype with 2n=48 chromosomes only in the Jaguariaíva basin; (e) the composition, location and nature of heterochromatic sites present in the A. janeiroensis karyotype of Ribeira basin and; (f) a possible sinapomorphic condition in the Characidium species with heteromorphic sex chromosome system. We also discussed the possible faunes interchange in the headwaters regions of Ribeira de Iguape and Tibagi rivers in the Ponta Grossa arc region, beside to the supposed endemic ictiofaune of Jaguariaíva basin. Thus, this study associated cytogenetic data, biogeographic aspects, and evolutive biology of fishes species located in the headwaters of three Paraná State rivers.